2011
DOI: 10.1007/s10333-011-0271-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of climate change on basin-average annual typhoon rainfalls with consideration of multisite correlation

Abstract: The effects of climate change on synoptic scale storms like typhoons can have profound impacts on practices of water resources management. A stochastic multisite simulation approach is proposed for assessing the impact of climate changes on basin-average annual typhoon rainfalls (BATRs) under certain synthesized climate change scenarios. Number of typhoon events and event-total rainfalls are considered as random variables characterized by the Poisson and gamma distributions, respectively. The correlation struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Precipitation is one of the critical parameters that climate change will influence and that will induce risk, hence the following were studied in great detail in Taiwan: the land-sea breeze system that that facilitates the formation of diurnal rainfall events [34][35][36], and seasonal monsoon events, including Madden-Julian oscillation impacts on winter rainfalls, and the East Asian summer monsoon (aka Meiyu), under different climate scenarios [37,38]. The preliminary study of watershed typhoon rainfalls and extreme precipitation under climate change found that the 24-h duration precipitation depth for 20-year and 100-year extreme events are likely to increase, suggesting concerns about the current hydrologic designs of critical infrastructures [39][40][41][42]. The secondary effects of precipitation on several factors, such as landslides, where critical precipitation is a characteristic that triggers large-scale landslide events, were studied and considered in conjunction in order to understand the cause/effect relationships; they were also impact assessed using climate projection [43][44][45][46][47].…”
Section: Adaptation Research Policy Support and Advocacymentioning
confidence: 99%
“…Precipitation is one of the critical parameters that climate change will influence and that will induce risk, hence the following were studied in great detail in Taiwan: the land-sea breeze system that that facilitates the formation of diurnal rainfall events [34][35][36], and seasonal monsoon events, including Madden-Julian oscillation impacts on winter rainfalls, and the East Asian summer monsoon (aka Meiyu), under different climate scenarios [37,38]. The preliminary study of watershed typhoon rainfalls and extreme precipitation under climate change found that the 24-h duration precipitation depth for 20-year and 100-year extreme events are likely to increase, suggesting concerns about the current hydrologic designs of critical infrastructures [39][40][41][42]. The secondary effects of precipitation on several factors, such as landslides, where critical precipitation is a characteristic that triggers large-scale landslide events, were studied and considered in conjunction in order to understand the cause/effect relationships; they were also impact assessed using climate projection [43][44][45][46][47].…”
Section: Adaptation Research Policy Support and Advocacymentioning
confidence: 99%
“…A covariance matrix, which characterizes correlations of all possible pairs of two random variables, plays an important role in multivariate simulation. Wu et al (2012) assessed climate change impacts on basin-average annual typhoon rainfalls by simulating multi-site typhoon rainfalls with consideration of their multisite correlations. Wang and Ding (2007) developed a nonparametric multivariate kernel density model for multivariate daily flow generation.…”
Section: Introductionmentioning
confidence: 99%